PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN DALAM PEMBENTUKAN INTENSI PEMBELIAN KONSUMEN - Setiawati, Erma; Murwanti, Sri (Benefit, 2006)
The researcher is highly interested in many different opinions among some experts about theinfluence of service quality and customer satisfaction in establishing purchase intentions. Thus, thepurpose of this research is to test such three variables, based on the model proposed by Taylor andBaker (1994) by interacting variables of quality service and customer satisfaction in establishing thepurchase intention with customer satisfaction as a moderator variable between service quality andpurchase intentions. This research was conducted in Surakarta with research object of two supermarkets. From the200 questionnaires distributed 188 were return.The result of the research indicate that regression coefficient of interaction among one supermarket (alfa) is positive and significant (pâ¤ 0.05), while onesupermarket (Goro Assalam) is not significant. The value of R2 for two supermarkets was increasingafter the interaction of service quality and customer satisfaction being participated in the model ofmoderator regression equality and the result supported in research hypothesis.